The Impact of Highly Qualified Teacher-Librarians in BC - Lee, Janelle (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
The levels of teacher-librarian formal education and training in British Columbia (BC) can vary, from a master’s degree in library and information studies, to teacher-librarianship diploma or teacher-librarianship certificate, to no formal education. There is substantial literature on the significance of having highly qualified, full-time teacher-librarians at schools, but most of the current literature exists outside of BC, and the definition of what highly qualified means is often very vague. This review will explore the existing literature on teacher-librarian qualifications to consider the need for further research into teacher-librarian qualifications in BC—specifically distinguishing how different levels of qualifications correlate with the teacher-librarian’s level of impact on their respective school communities, which could also provide evidence and support for the need for more highly qualified teacher-librarians in BC.